2017
DOI: 10.1002/wat2.1268
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics: An introduction to environmental transport processes

Abstract: Microplastic pollution is widespread across the globe, pervading land, water, and air. These environments are commonly considered independently, however, in reality these are closely linked. This review gives an overview of the background knowledge surrounding sources, fate and transport of microplastics within the environment. We introduce a new “Plastic Cycle” concept in order to better understand the processes influencing flux and retention of microplastics between and across the wide range of environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
211
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 451 publications
(219 citation statements)
references
References 76 publications
3
211
0
5
Order By: Relevance
“…However, whilst seafloor microplastics have since been documented in an increasing number of studies, this has been done on a largely ad hoc basis, using existing cores and samples from older studies. Attention has been paid to ingestion of microplastics by seafloor organisms, however, there has been extremely limited attention paid to the physical mechanisms that control how microplastics reach the seafloor, how they are distributed and what governs their ultimate fate (e.g., Gregory, 2009;Corcoran et al, 2017;Graca et al, 2017;Horton and Dixon, 2017). Process-based sedimentological studies routinely relate sediment and other particulate accumulations to the processes that transport, deposit, and bury them.…”
Section: Introduction: What Are Microplastics and Why Do We Care?mentioning
confidence: 99%
See 1 more Smart Citation
“…However, whilst seafloor microplastics have since been documented in an increasing number of studies, this has been done on a largely ad hoc basis, using existing cores and samples from older studies. Attention has been paid to ingestion of microplastics by seafloor organisms, however, there has been extremely limited attention paid to the physical mechanisms that control how microplastics reach the seafloor, how they are distributed and what governs their ultimate fate (e.g., Gregory, 2009;Corcoran et al, 2017;Graca et al, 2017;Horton and Dixon, 2017). Process-based sedimentological studies routinely relate sediment and other particulate accumulations to the processes that transport, deposit, and bury them.…”
Section: Introduction: What Are Microplastics and Why Do We Care?mentioning
confidence: 99%
“…Insets show the potential distribution and transport vectors of microplastics in (A) a channel-levee system and (B) a bottom current moat and drift system, respectively. Modified and extended (to include marine realm) fromHorton and Dixon (2017). WWT, waste water treatment.…”
mentioning
confidence: 99%
“…Microplastics (including synthetic fibres) \ 5 mm in size are of interest due to the likelihood of ingestion by freshwater organisms and, because they have large specific surface area, their potential for adsorption and leaching of associated contaminants and additives (Lobelle and Cunliffe 2011;Sanchez et al 2014;Faure et al 2015;Näkki et al 2017). Pellets and 'microbeads' specifically manufactured as microplastic forms (primary microplastics) may be found in freshwaters subject to large inputs of industrial drainage or effluent (Castañeda et al 2014;Lechner et al 2014;Corcoran et al 2015;Driedger et al 2015;Baldwin et al 2016;Horton et al 2017a;Horton and Dixon 2018), although secondary microplastics (derived from the breakdown of larger plastic items) dominate in freshwater sediments subject to more diffuse plastic waste sources (Free et al 2014;Driedger et al 2015;Faure et al 2015;Zhang et al 2016;Blettler et al 2017;Matsuguma et al 2017;Sruthy and Ramasamy 2017;Imhof et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Oceans are often considered the endpoint of plastic fluxes from hydrological catchments (Horton & Dixon, 2017). As highlighted previously, it is estimated that fluxes of plastics from rivers provide a major input of macro-and microplastics into marine environments across the globe (Lebreton et al, 2017;UNEP, 2016).…”
Section: Marine Systemsmentioning
confidence: 99%
“…Indeed, recent reviews and theoretical models have indicated a large number of potential sources, fluxes and sinks of plastics across the wider environment (Alimi, Farner Budarz, Hernandez, & Tufenkji, ; Browne et al, ; de Souza Machado, Kloas, Zarfl, Hempel, & Rillig, ; Horton, Svendsen, Williams, Spurgeon, & Lahive, ; Wagner et al, ). While crude estimates of environmental plastic fluxes have been attempted, a more detailed understanding of the sources, fluxes and effects of these anthropogenic pollutants in time and space, and a more comprehensive quantification of their fate, is now required urgently to determine the risks to people and ecosystems across the globe (de Souza Machado, Kloas et al, ; Horton & Dixon, ; Nizzetto, Bussi, Futter, Butterfield, & Whitehead, ).…”
Section: Introductionmentioning
confidence: 99%